2008
DOI: 10.1007/s00394-007-0690-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of black and green tea consumption on blood glucose levels in non-obese elderly men and women from Mediterranean Islands (MEDIS epidemiological study)

Abstract: Tea consumption is associated with reduced levels of fasting blood glucose only among non-obese elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 26 publications
4
38
0
6
Order By: Relevance
“…One study observed a borderline inverse association between magnesium intake and risk of type 2 diabetes. However, magnesium did not explain the relation between coffee and type 2 diabetes in our study, similar to other studies [30,[34][35][36]. In our study up to three cups of coffee was associated with higher blood pressure, but more than four cups of coffee was associated with a lowered blood pressure.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…One study observed a borderline inverse association between magnesium intake and risk of type 2 diabetes. However, magnesium did not explain the relation between coffee and type 2 diabetes in our study, similar to other studies [30,[34][35][36]. In our study up to three cups of coffee was associated with higher blood pressure, but more than four cups of coffee was associated with a lowered blood pressure.…”
Section: Discussionsupporting
confidence: 81%
“…Although we could not differentiate between black and green tea, an estimated 95% of the total tea consumption is black tea in the Netherlands [25]. Recently, a study reported that both black and green tea lower blood glucose concentrations [34]. Combined with our results, it seems likely that the association between tea consumption and type 2 diabetes is not solely due to consumption of green tea.…”
Section: Discussionsupporting
confidence: 46%
“…Seven studies were excluded because they were other design types. 24,25,[35][36][37][38][39] A study by Mackenzie et al 40 was excluded because some participants had diabetes at baseline. Two articles were excluded because they did not provide 95% CI or data to calculate (Fig.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…22 Another study provided evidence that green tea promoted glucose metabolism in healthy humans and produced an antihyperglycemic effect in diabetic mice. 24 A population-based, case-control study by Polychronopoulos et al 25 reported that tea consumption could reduce levels of fasting blood glucose in nonobese elderly people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation